2021
DOI: 10.1002/edn3.229
|View full text |Cite
|
Sign up to set email alerts
|

The state, transport, and fate of aboveground terrestrial arthropod eDNA

Abstract: Environmental DNA (eDNA) analyses have become invaluable for detecting and monitoring aquatic and terrestrial species and assessing site biodiversity within aquatic environments or soil. Recent studies have extended these techniques by using eDNA to identify the presence of aboveground terrestrial arthropods directly from vegetative surfaces. However, while the dynamics of eDNA state, transport, and fate (its “ecology”) have been explored within aquatic environments and soil, they have yet to be explored withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…Overall, these results prove that most species detected within the rainwash water were eDNA signals washed into the sampler from the tree canopy. This aligns with results reported by Valentin et al (2021) showing that invertebrate eDNA is washed off vegetation surfaces and can be detected. However, it is highly likely that only a very small proportion of the eDNA released by the invertebrate community in the canopy was detected in rainwash eDNA, since the samplers only covered an area of 1 m 2 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, these results prove that most species detected within the rainwash water were eDNA signals washed into the sampler from the tree canopy. This aligns with results reported by Valentin et al (2021) showing that invertebrate eDNA is washed off vegetation surfaces and can be detected. However, it is highly likely that only a very small proportion of the eDNA released by the invertebrate community in the canopy was detected in rainwash eDNA, since the samplers only covered an area of 1 m 2 .…”
Section: Discussionsupporting
confidence: 92%
“…However, the potential of eDNA metabarcoding of rainwater to assess canopy insect diversity has not been explored. Valentin et al (2021) investigated the effect of rain on the fate of arthropod eDNA and found that rainfall or mist removes most terrestrial eDNA present on vegetation surfaces. Building on this idea, we performed a simple proof-of-principle analysis and hypothesized that (i) using a rainwash sampler, canopy invertebrates can be detected reliably by eDNA metabarcoding of the collected water shortly after a rain event, and that (ii) the taxonomic composition of collected communities will differ between the tree host taxa, with distinct host-specific invertebrates being found below different canopies.…”
Section: Introductionmentioning
confidence: 99%
“…There are still many questions regarding the efficacy of eDNA metabarcoding as a tool for biomonitoring that remain unanswered or underexplored. While studies have been conducted over a range of terrestrial ecosystems (e.g., tropical to arctic, Bohmann et al, 2014), aquatic studies still dominate (Barnes et al, 2014;Strickler et al, 2015;Tsuji et al, 2017;Williams et al, 2018), and the effects of abiotic variables on terrestrial eDNA longevity and transport remain mostly unexplored (Valentin et al 2021). Studies focusing on water samples suggest UV, pH, temperature, and bacterial abundance all have an impact on eDNA longevity (Barnes et al, 2014;Strickler et al, 2015;Tsuji et al, 2017;Williams et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally overlooked during the excitement of the latest, innovative eDNA application is the fact that eDNA itself represents an ecological entity worthy of study in its own right. After an organism sheds genetic material, but before a researcher or manager collects it, eDNA interacts with its surrounding environment in myriad ways that influence its production and accumulation (e.g., Maruyama et al, 2014;Klymus et al, 2015), changes in form and state in the environment (e.g., Jo et al, 2019;Barnes et al, 2021), transport (e.g., Andruszkiewicz et al, 2019;Valentin et al, 2021), and ultimately its fate (e.g., Tsuji et al, 2017;Foucher et al, 2020). Collectively, Barnes and Turner (2016) referred to these dynamic processes and functions as "the ecology of eDNA, " and they shape the inferences that researchers and managers can make based on detection (or non-detection) events.…”
Section: Foundationmentioning
confidence: 99%